Management Behaviour on Dividend Payouts: An Overview of the Spanish and British Quoted Corporations - Dominguez Munoz, Celia (2005)
This paper describes the management behaviour of Spanish and British quoted corporations on setting company dividend payouts. To do so, the author surveys CFOs in the two countries to capture their views about dividend policy relevancy; the factors that drive their dividend decisions and the determinants of their dividend payouts. The findings show that managers stress the importance of dividend policy in the firm's value and give the strongest support to the signalling and 'bird-in-the-hand' explanations. They provide however, very little support for the Agency and Tax Issues. Whereas managers in the UK show the highest level of uncertainty in the Clientele effect, Spanish respondents agree with it. The paper does not capture the Behavioural approach. Although in general terms respondents show similar patterns of behaviour, the author finds important differences in aspects of corporate governance and legal tax systems that help to determine whether such behaviour fits into the country's traits and the finance literature.